Nos rastros de Limite : um estudo de caso na história da preservação das imagens em movimento no Brasil - Vasques, Alexandre Ramos (Universidade Federal de São Carlos, 2012)
The theme of this work is the film preservation in Brazil and its focus is the film preservation history of Limite (Mário Peixoto, 1931). In the introduction we situate our research within a Brazilian reality of appreciation of academic studies on the preservation of moving images, showing, in advance, some works, produced recently that have become fundamental sources of consultation in our research. In addition to the technical and historical sources, we also present in our bibliographic clipping related to Limite. The origins of our primary sources of research, filmic materials of Limite are also reported in the first lines of our work. In the first chapter of our work we try to approach the field of audiovisual archiving reader, describing each of the technical terms and concepts relevant to the preservation and restoration of audiovisual used throughout the text. In the second chapter, we give an account of contemporary Limite production years, and also of his rare nitrate copy views. The third chapter addresses issues related to the process of restoring physical chemistry of Limite s filmic materials, demand created by precarious conditions presented by the nitrate copy of the film, extending up to the purchase of materials and direct films on the work by Embrafilme, in 1980. The fourth chapter presents and analyzes some stretches of finegrain print, masters and master copy examined during our research, creating the necessary conditions to draw some conclusions about the handling incurred by work, dating from 1930 until 1980.
Keywords: Cinema; Filmes - preservação e conservação; Cinematografia - conservação e restauração; Cinemateca brasileira; Museu de Arte Moderna do Rio de Janeiro (Rio de Janeiro, RJ); Cinema; Audiovisual preservation; Restoration; Audiovisual; Cinemateca Brasileira; Cinemateca do MAM; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA